2014
DOI: 10.2217/nnm.13.122
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Implants Equipped with ’Fish Scale‘-Like Nanoreservoirs of Growth Factors for Bone Regeneration

Abstract: Implants triggering rapid, robust and durable tissue regeneration are needed to shorten recovery times and decrease risks of postoperative complications for patients. Here, we describe active living collagen implants with highly promising bone regenerative properties. Bioactivity of the implants is obtained through the protective and stabilizing layer-by-layer immobilization of a protein growth factor in association with a polysaccharide (chitosan), within the form of nanocontainers decorating the collagen nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Recently, we reported that it is possible to incorporate active growth factors (BMP-2, TGF-β1) as nanoreservoirs to induce bone formation. 20,21,[44][45][46] We have also shown that electrospun thin PCL membranes (50 μm) increase the speed of bone regeneration when they incorporate BMP-2 within nanocontainers. We also showed no passive uncontrolled release of those growth factors from the active nanocontainers, but an active cell contact-dependent release.…”
mentioning
confidence: 80%
“…Recently, we reported that it is possible to incorporate active growth factors (BMP-2, TGF-β1) as nanoreservoirs to induce bone formation. 20,21,[44][45][46] We have also shown that electrospun thin PCL membranes (50 μm) increase the speed of bone regeneration when they incorporate BMP-2 within nanocontainers. We also showed no passive uncontrolled release of those growth factors from the active nanocontainers, but an active cell contact-dependent release.…”
mentioning
confidence: 80%
“…In addition to the bioaffinity of ECM components, the architecture of ECM microenvironments also plays a pivotal role in directly modulating GF activity and cell fate during tissue repair (Figure 1c3). Eap et al 49 constructed biomimetic ECM nanostructures for the immobilization of BMP-2 by assembling polysaccharides (chitosan) on collagen nanofibers. Both in vitro and in vivo evaluations confirmed that this sophisticated strategy enhanced the safety and efficacy of the therapeutic matrix in terms of bone formation compared to the more simplistic, traditional approaches based on immersion of the substrates with GFs.…”
Section: Ecm-inspired Gf Delivery Systemsmentioning
confidence: 99%
“…As proteins secreted by cells, growth factors act on critical functions as cell division, matrix synthesis and tissue differentiation [31,32], and play important roles in healing of bone fractures [33]. These bone growth factors include bone morphogenetic protein (BMP), vascular endothelial growth factor (VEGF), broblast growth factor (FGF), transforming growth factor-β (TGF-β) and so on.…”
Section: Ngf Accelerates Healing Of Mandible Fracturementioning
confidence: 99%